Japanese guidance for use of biologics for psoriasis (the 2019 version) - Saeki, Hidehisa; Terui, Tadashi; Morita, Akimichi; Sano, Shigetoshi; Imafuku, Shinichi; Asahina, Akihiko; Komine, Mayumi; Etoh, Takafumi; Igarashi, Atsuyuki; Torii, Hideshi; Abe, Masatoshi; Nakagawa, Hidemi; et al. (Journal of dermatology, 2020)
As the first biologics for psoriasis in Japan, infliximab and adalimumab, anti‐tumor necrosis factor‐α antibodies, became available in the field of dermatology in 2010, followed by ustekinumab, an anti‐interleukin (IL)‐12/IL‐23p40 antibody, which was launched in Japan in 2011. Since 2015, three IL‐17 inhibitors of secukinumab and ixekizumab, anti‐IL‐17A antibodies, and brodalumab, an anti‐IL‐17 receptor antibody, and two anti‐IL‐23p19 antibodies of guselkumab and risankizumab, have also been launched. It is important for physicians to select appropriate biologic therapy for each psoriatic patient after due consideration of disease factors, treatment factors and patient background factors, sharing such information with patients. The following can be listed as points to be considered for the selection of biologics: drug effects (e.g. strength of effectiveness, time to onset of effectiveness, effectiveness against arthritis, primary failure, secondary failure), safety (e.g. infections, administration‐related reactions and relationships with other comorbidities), convenience for patients (e.g. hospital visit intervals, self‐injection, maintenance therapy at clinics, feasibility of drug discontinuation/re‐administration) and payment (medical costs) borne by patients. This guidance has been prepared with the aim of allowing dermatologists experienced in the treatment of psoriasis to use biologics appropriately according to the circumstances of individual patients after consideration of the above‐mentioned factors.